Analysis of Eye Donation Awareness in Engineering Students - Pandey, Krishna Mohan; Kumar, Vivek (International Journal of Computer Sciences and Engineering, 2025)
Eye is the most valuable part of our body without the eye sight one cannot feel the beauty of this world. There are a lot of people who aware about the eye donation. In medical area almost everyone know this term and they are already aware and they are also aware the society. But if we are looking at the engineering area then we feel that the number of students and engineers are not very much aware about eye donation. The main cause of blindness is corneal diseases. Blindness can be removed if we have a number of eye donors, for this we have to aware about the eye denotation in each area. We must aware and motivate the people for eye donation by which we can decrease the number of blind persons.